دراسة تشريحية وباليونولوجية لنوعين من جنس اللاميومLamium L. (L. moschatum Mill. و L. striatum Sibth. et Smith. ) من الفصيلة الشفوية Lamiaceae - لايقة سرحان; قره علي أحمد; سلطان عبير (Latakia University Journal -Biological Sciences Series, 2019)
تم إجراء دراسة تشريحية وباليونولوجية للنوعينL. moschatum Mill. وL. striatum Sibth. et Smith.. تبين من خلال الدراسة الباليونولوجية أن حبات الطلع كانت ثلاثية خطوط الإنتاش وقطرها يتناسب طرداً مع طول الزهرة ، وأفضل إنتاش لها كان في الدرجة 25مْ للنوع الأول و20مْ للنوع الثاني . أظهرت الدراسة التشريحية للورقة وجود النسيج الحباكي تحت البشرة العلوية فقط في منطقة القرص، وكثرة الأوبار اللامسة متعددة الخلايا على صف واحد والمفرزة من نمط الغدد ذات القاعدة متعددة الخلايا وذات الرأس رباعي وثماني الخلايا . توجد فضوة كبيرة في مركز ساق النوع الأول ، وصغيرة في النوع الثاني ويتوضع الكولانشيم في زوايا مقطعه المربع . Anatomical and palynological study of two species of genus Lamium L. (Lamiaceae): Lamium moschatum Mill. and Lamium striatum Sibth. et Smith were effected . The palynological study reveals that the pollens had three germination lines and its diameter is direct according to the length of flower , and the best germination was in 25c for L.moschatum Mill. and 20c for the other . The anatomical study of leaf showed that there is palisade tissue under the upper epidermis only in disk area and enormous multi cellular feeler hairs on one class , secretory glandular hairs with multi cellular base and with tetracellular and eight cellular head . There is a big lacuna in the center of the stem of L.moschatum Mill. and a small lacuna in the other species . The collenchymas is located in the angles of the quadrate section .